User experience over time - Karapanos, Evangelos; Hassenzahl, Marc; Martens, Jean Bernard O.S. (My University, 2008)
The way we experience and evaluate interactive products develops over time. An exploratory study aimed at understanding how users form evaluative judgments during the first experiences with a product as well as after four weeks of use. Goodness, an evaluative judgment related to the overall satisfaction with the product, was largely formed on the basis of pragmatic aspects (i.e. utility and usability) during the first experiences; after four weeks of use identification (i.e. what the products expresses about its owner) became a dominant aspect of how good a product is. Surprisingly, beauty judgments were largely affected by stimulation (e.g. novelty) during the first experiences. Over time stimulation lost its power to make the product beautiful in the users' eyes.
Keywords: Longitudinal; Product appraisal; User experience